Menggali Potensi Daerah Dengan Pengembangan Potensi Kesenian Serta Edukasi Wisata Melalui Program KKNT di Desa Carangwulung - Nuriah Yuliati; Alfian Farrel A.L; Ameta Novelia Br Karo; Ana Safira Putri; Choirul Miftakhul Anam; Mohammad Idhom (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Every country has distinctive characteristics that become selling points in terms of economy and infrastructure, including small regions such as districts, sub-districts, villages, and hamlets that need to be developed to be more widely known. These distinctive values, including natural potential, plantation products, micro-businesses, tourism sectors, and arts, are important for regional existence. Carangwulung Village in Wonosalam Sub-district, Jombang Regency, has high natural potential such as durian, salak and coffee. Located in the highlands, the village excels in plantations. The tourism sector stands out with its beautiful environment and friendly people, making it an ideal destination for tourists. Plantation products are processed into high-value products through MSME businesses that prioritize quality. Arts potential, such as Gamelan, Jaranan, and Remo Dance, are also preserved. The community service program focused on the development of arts and tourism in Carangwulung Village, including the "Selepas Senja" art performance and tourism. The research used a qualitative descriptive methodology, collecting data through observation, interviews and FGDs. The findings show the importance of preserving and promoting local coffee culture and traditional arts to attract tourists. The eco-tour involved 10 UPN "Veteran" East Java students and the local community.